Harm production and the moral dislocation of finance in the city of London : an ethnography - Simpson, Alex (Emerald Publishing Limited, 2021)
This book is about disconnection. Disconnection gives vision to the City of London as an insulated social arena that, despite creating vast wealth and being the vanguard of the UK's aspirational future, has made objects out of you and me. Building on Foucault's teachings on finance and the ideological force of market competition, this ground-breaking book gives shape and form to how financial markets are sustained, managed and performed, and how they emerge and solidify within the shared cultural imagination and system of knowledge as a single, smooth, frictionless and coherent idea. Tracing the impacts of financialisation on those who enact its harmful logic, the author delves into the spatial disconnection that separates the City from the rest of London and the UK; the ontological disconnection that erects a demarcated boundary of expected outcomes, aspirations and practices; and the social disconnection experienced by finance workers who elevate themselves through a marker of perceived difference and ability. Through emerging narratives and ethnographic encounters, Simpson explores the practical and cognitive relations that underpin the performance of finance as a moral endeavour and analyses what it means to live and work within this extractive industry.
Keywords: Financialization -- Social aspects.; Capitalists and financiers -- Psychology.; Finance -- England -- London.; Social Science, Social Classes & Economic Disparity.; Social classes.; elektronické knihy; electronic books